2014
DOI: 10.1002/sec.1010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and improvement of a multi-factor biometric authentication scheme

Abstract: In order to enhance the security in wireless communication, authentication schemes come to be more crucial and widely deployed recently, especially those which are referred to as multi-factor biometric authentication that base on password, biometrics, and smart card protections. A new scheme in this way was proposed in 2010 by Li and Hwang. Then Das extended the work of Li et al. and made an improvement of their weak scheme in 2011. However, in 2012, Younghwa An demonstrated that Das's protocol failed to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…In addition, the running time of XOR operation is rather low, and we thus ignore the timing results. We can see that previous schemes 18,19,21 are more efficient than other schemes since they do not use Diffie-Hellman key exchange. Compared with Park et al's 24 scheme, our scheme consumes more computation resources for providing stronger security guarantee, but we think the additional computation cost is acceptable and worthwhile.…”
Section: Performance Evaluationmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, the running time of XOR operation is rather low, and we thus ignore the timing results. We can see that previous schemes 18,19,21 are more efficient than other schemes since they do not use Diffie-Hellman key exchange. Compared with Park et al's 24 scheme, our scheme consumes more computation resources for providing stronger security guarantee, but we think the additional computation cost is acceptable and worthwhile.…”
Section: Performance Evaluationmentioning
confidence: 89%
“…However, An 19 pointed out that Das' scheme also cannot withstand impersonation attack and server spoofing attack. Although An 19 put forward a new three-factor authentication scheme, Khan and Kumari 20 demonstrated that this scheme cannot resist offline guessing attack, Cao and Ge 21 showed that this scheme is vulnerable to replay attack. Subsequently, Yeh et al 22 and Wu et al 23 further analyzed the security of these schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Wu 46 found that Xie et al's scheme 45 is vulnerable to desynchronization attacks, and proposed an improvement. 35 (A2, A3) 37,38 Choi et al 37 -Park et al 38 (A3, A4) 39 Zhao et al 39 -…”
Section: Single-server Environmentmentioning
confidence: 99%
“…Similarly, in protocol [17], the smart privileged insider attacker who knows , 1 , and in registration phase can impersonate a legal user. Similarly, in protocol [16], the smart privileged insider attacker of the registration center who knows , , and can impersonate a legal user. Wu et al [17] have illustrated many weaknesses of protocol [19].…”
Section: Resistance To the Smart Privileged Insider Attackmentioning
confidence: 99%